É possível um curso superior de tecnologia em marketing propor em seu currículo o consumo sustentável? - Zanoni, Eliane (2018)
This study, developed in the context of the research line of the New Technologies in Education, by the Education Program: Curriculum, of the Pontifical Catholic University of São Paulo, aims to reflect on the directives of the General National Curricular Guidelines for the organization and operation of Superior Courses of Technology about the conscious consumption and socially responsible to subsidize the construction of the Pedagogical Projects of the Superior Courses of Technology in Marketing. The research had as general objective to analyze the existence of the formation of professional awareness of the social-environmental consequences of consumerism in the curriculum of the superior course of technology in marketing. For this analysis, topics related to curriculum, superior courses of technology, and superior course of technology in Marketing, as well as marketing and consumption were addressed. The methodology includes a bibliographical study of the topics addressed and a documentary research based on the analysis of the legislations and institutional documents of the course in focus. The results of the research allowed to know in a broader way the conceptions about what the General National Curricular Guidelines for the organization and the operation of the superior courses of technology alude about the consumption consciously and socially responsible to subsidize the construction of the Pedagogical Projects of the superior courses of technology in Marketing. In tune, it identified the elements of formation directed to the conscious consumption from the curriculum of the superior course of technology in Marketing researched, pointing out the main practices used and how they present themselves. Finally, the possibilities of improvement in the curriculum of the Marketing course, directed to the formation of a professional that, besides the function of studying and proposing indiscriminate ways of selling, is concerned with the formation of values of conscious and socially responsible consumption